Natural antimicrobials for the minimal processing of foods - Roller, Sibel (Woodhead Publishing Limited and CRC Press LLC, 2011)
Natural Antimicrobials for the Minimal Processing of Foods discusses their practical application in food preservation. Topics covered include: the use of bacteriocins in preserving animal and other food products; the current and future uses of certain preservatives; and the use of natural antimicrobials in edible coatings. Three chapters are devoted to antimicrobials from plants and their use in a wide range of applications. With its practical emphasis and authoritative coverage, this book will be a standard work for the food industry in developing new preservation systems that extend the shelf life of foods without compromising safety or sensory quality.